UPAYA PENINGKATAN KOMPETENSI GURU DALAM PEMANFAATAN TEKNOLOGI PADA KEGIATAN PEMBELAJARAN - Bhismantara, Bramanti Sancaka; Iskandar, M. Yakub; Wijayanti, Hendrika Tri; Widiastuti, Anik; Wulandari, Taat; Rokhim, Hanif Nur (Jurnal Manajemen Pendidikan, 2024)
In this 4.0 era, the development of Science and Technology (IPTEK) cannot be separated from every area of ​​life. The role of science and technology is to participate in facilitating and building every implementation of the ideals of independence, one of which is in the field of education. This article aims to empower and improve teachers' ability to master Information and Communication Technology (ICT) as a support for learning, considering that the limited ability to master technology among teachers in Indonesia is still a problem. The research method used is through literature studies that are conceptual in nature and related to ideas and theoretical studies. The ICT capabilities possessed by teachers will help in the process of creating all the components needed for teaching in order to improve the quality of learning in the era of globalization. This article uses a literature study method through collecting library data to produce an idea or thoughts. It is hoped that this article can be an effort to improve teachers' ability to utilize technology in their role as educators, because massive technological advances would be a shame if they were not balanced with the readiness of human resources regarding mastery skills.